Military Wives' Transition and Coping: Deployment and the Return Home - Marnocha, Suzanne (International Scholarly Research Network, 2012)
The objective of this qualitative study is to explore the experiences of wives of deployed soldiers. Semistructured interviews were used to answer the research questions. Meleis' Transitions Theory was used to guide the understanding of the wives' experiences. Phase One: news of deployment, property of awareness, themes of emotional chaos and making preparations. Phase Two: during deployment, property of engagement, themes of taking the reins and placing focus elsewhere, along with the property of change and difference, with themes of emotional and physical turmoil, staying strong, and reaching out. Phase Three: after deployment, property of time span, themes of absence makes the heart grow fonder and reestablishing roles. The study concluded that the wife often feels forgotten during deployment. Nurses can give better care by understanding how the different phases of deployment and separation affect the wife's coping ability and her physical and emotional health.